TEENAGE MARRIED PREGNANCY: ANALYSIS OF 400 PATIENTS IN SOUTHERN IRAN - Nisa, Rahat -un-; Khairandeish, M.H.; Mazloom, K. (Journal of Ayub Medical College Abbottabad, 2024)
Abstract: Four hundred married teenage pregnant patients were interviewed at the time of admission for labour to the obstetrical service of Shiraz University Medical Centre, Shiraz, Iran. Their prenatal course, method of delivery, hospital course, and pregnancy outcome were reviewed. The majority of patients were not registered for prenatal care and had been referred to the Medical Centre after complicated labour had developed. Generally, these patients represented the lower socio-economic level, had minimal educational background, lacked information and motivation for contraception or prenatal care and in many cases were treated by poorly trained midwives as normal obstetrical patients, hence the high incidence of pregnancy complications, difficult deliveries and fetal morbidity and mortality. Forty per cent of the patients represented a changing social movement in Iran from rural nomadic existences to industrialization and urbanization.